Waste Management In UIN Sumatera Utara (A Transdicipliner Approach) - Sukiati Sukiati (IAIN Padangsidimpuan, 2019)
This study aims to describe the waste management at UIN North Sumatra Campus. This research is a qualitative research. Data collected by observation and interview. Several strategies were carried out in this research, namely the sensitization of awareness through campaigns, training and action by forming forums and movements. The results of this study were analyzed with approach 3 (three approaches); Islamic Theology of Waste Management; Moral and Character Education Approach in Waste Management and Social Approach to Waste Management. By a theological approach, waste management should be approached with the belief that paying attention to waste must be based on the belief that it is all at the command of God and His apostles. The character approach implies that caring for this, is a good character and integral to his theological beliefs. The social approach gives awareness to the attitude that waste is not something that is simply ignored but must be a concern and be carried out with integrated cooperation